Experiences from the Brazilian Atlantic Forest: ecological findings and conservation initiatives. Issue 3 (10th September 2014) - Joly, Carlos A.; Metzger, Jean Paul; Tabarelli, Marcelo
Summary: The Brazilian Atlantic Forest hosts one of the world's most diverse and threatened tropical forest biota. In many ways, its history of degradation describes the fate experienced by tropical forests around the world. After five centuries of human expansion, most Atlantic Forest landscapes are archipelagos of small forest fragments surrounded by open‐habitat matrices. This 'natural laboratory' has contributed to a better understanding of the evolutionary history and ecology of tropical forests and to determining the extent to which this irreplaceable biota is susceptible to major human disturbances. We share some of the major findings with respect to the responses of tropical forests to human disturbances across multiple biological levels and spatial scales and discuss some of the conservation initiatives adopted in the past decade. First, we provide a short description of the Atlantic Forest biota and its historical degradation. Secondly, we offer conceptual models describing major shifts experienced by tree assemblages at local scales and discuss landscape ecological processes that can help to maintain this biota at larger scales. We also examine potential plant responses to climate change. Finally, we propose a research agenda to improve the conservation value of human‐modified landscapes and safeguard the biological heritage of tropical forests. Contents Summary 459 I. Introduction 459 II. The Atlantic Forest: a highly diverse, relevant and threatened forest 460 III. Biotic homogenization and forest secondarization 462 IV. Species persistence at larger scales 464 V. Future threats: climate change impacts 466 VI. Atlantic Forest conservation: integrating basic and applied research agendas 467 VII. Concluding remarks 469 Acknowledgements 469 References 469